A Low-Cost Portable Lidar-based Mobile Mapping System on an Android Smartphone - J. Huai; Y. Shao; Y. Zhang; A. Yilmaz (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The rapid advancement of the metaverse, digital twins, and robotics underscores the demand of low-cost, portable mapping systems for reality capture. Current mobile solutions, such as the Leica BLK2Go and lidar-equipped smartphones, either come at a high cost or are limited in range and accuracy. Leveraging the proliferation and technological evolution of mobile devices alongside recent advancements in lidar technology, we introduce a novel, low-cost, portable mobile mapping system. Our system integrates a lidar unit, an Android smartphone, and a GNSS-RTK stick. Running on the Android platform, it features lidar-inertial odometry built with the NDK, and logs data from the lidar, wide-angle camera, IMU, and GNSS. With a total bill of materials (BOM) cost under $2,000 and a weight of about 1 kilogram, the system achieves a good balance between affordability and portability. We detail the system’s design, multisensor calibration, synchronization, and evaluate its performance for 3D reconstruction, focusing on tracking and mapping accuracy. To further contribute to the community, the system’s design and software will be made open source.